Kesamaptaan dan Efektivitas Pelaksanaan Tugas: Analisis Korelasi Kesiapan Fisik dan Keberhasilan Operasional pada Lingkungan TNI Wilayah Lubuk Pakam - Sifana, Shabani Adila; Sembiring, Zamalludin (Lembaga Yasin AlSys, 2025)
This study is motivated by the importance of physical fitness in supporting the daily duties of Indonesian National Army (TNI) soldiers, who routinely engage in physical training before carrying out operational tasks. The purpose of this research is to analyze the relationship between soldiers’ physical readiness and the effectiveness of task execution within the TNI units in the Lubuk Pakam area. A qualitative approach was used, with data collected through in-depth interviews, field observations, and documentation studies. The research explores soldiers’ perceptions and experiences regarding the impact of physical fitness on the success of military duties. The results indicate that physical readiness significantly affects not only endurance and agility but also morale, discipline, and adaptability in facing dynamic operational situations. Factors such as motivation, stress management, use of supportive technology, and consistency in physical training further strengthen the link between fitness and task effectiveness. The success of task execution related to physical readiness is reflected in six key indicators: rapid response in emergencies, success in field missions, endurance in challenging terrain, minimal injury during operations, mental resilience and high discipline, and team solidarity in completing tasks. The conclusion of this study affirms that physical fitness development is a strategic component that is inseparable from efforts to enhance the effectiveness of military task execution within TNI units.